Preoperative anxiety management in pediatric patients: a systemic review and meta-analysis of randomized controlled trials on the efficacy of distraction techniques - Mustafa, Muhammad Saqlain; Shafique, Muhammad Ashir; Zaidi, Syeda Dua E Zehra; Qamber, Amna; Rangwala, Burhanuddin Sohail; Ahmed, Aftab; Zaidi, Syeda Mahrukh Fatima; Rangwala, Hussain Sohail; Uddin, Muhammad Musab Nafees; Ali, Mirha; Siddiq, Mohammad Arham; Haseeb, Abdul (Frontiers in Pediatrics, 2024)
This study addresses the pervasive issue of heightened preoperative anxiety in healthcare, particularly among pediatric patients. Recognizing the various sources of anxiety, we explored both pharmacological and nonpharmacological interventions. Focusing on distraction techniques, including active and passive forms, our meta-analysis aimed to provide comprehensive insights into their impact on preoperative anxiety in pediatric patients.Following the PRISMA and Cochrane guidelines, this meta-analysis and systematic review assessed the efficacy of pharmaceutical and distraction interventions in reducing pain and anxiety in pediatric surgery. This study was registered on PROSPERO (CRD42023449979).This meta-analysis, comprising 45 studies, investigated pharmaceutical interventions and distraction tactics in pediatric surgery. Risk of bias assessment revealed undisclosed risks in performance and detection bias. Distraction interventions significantly reduced preoperative anxiety compared to control groups, with notable heterogeneity. Comparison with Midazolam favored distraction techniques. Subgroup analysis highlighted varied efficacies among distraction methods, with a notable reduction in anxiety levels. Sensitivity analysis indicated stable results. However, publication bias was observed, suggesting a potential reporting bias.Our study confirms distraction techniques as safe and effective for reducing pediatric preoperative anxiety, offering a valuable alternative to pharmacological interventions.